Pembuatan Ecobrick sebagai Bentuk Ramah Lingkungan dalam Mengembangkan Motorik Halus pada Anak Usia Dini 4-6 Tahun di Desa Jatirejo Kabupaten Pasuruan - Lilis Nabila Aisyah; Ilun Mualifah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to describe the implementation of ecobrick activities as an environmentally friendly initiative and as a strategy to enhance fine motor development in early childhood aged 4-6 years in Jatirejo Village, Pasuruan Regency. This research employed a descriptive qualitative approach using observation, interviews, documentation, and hands-on ecobrick practice. The findings indicate that the ecobrick process-which includes collecting plastic waste, washing, drying, cutting, inserting plastic pieces into bottles, and compressing the contents-effectively improves children’s fine motor skills, particularly in hand-eye coordination, finger strength, accuracy, and cutting ability. Children demonstrated positive responses, including high enthusiasm, curiosity, and increased awareness of environmental preservation. The activity also strengthened children’s social development through cooperation, communication, and shared responsibility. Overall, ecobrick activities function not only as an innovative waste-management solution but also as an educational medium that holistically supports child development and instills environmental awareness from an early age.